A new Ryukyuan species of Edaphus Motschulsky (Coleoptera, Staphylinidae, Euaesthetinae) - Jałoszyński, Paweł; Sapieja, Mateusz (Zootaxa, 2022)
Edaphus nagugushikuensis sp. n., a new Japanese rove beetle species of the subfamily Euaesthetinae is described and illustrated based on a male specimen collected in the northern region of Okinawa-jima, Okinawa Prefecture, Japan. It is the 56th species of Edaphus Motschulsky known to occur in Japan, and the sixth known to inhabit the largest Ryukyuan island. Puthz’s identification key to Edaphus species of the southwestern Japanese islands from 2010 is modified to include the new species.